Exposure therapy consortium: Outcomes of the proof-of-principle study - Smits, Jasper A.J.; Abramowitz, Jonathan S.; Anderson, Rebecca A.; Arch, Joanna J.; Badeja, Daniel; Barzilay, Snir; Belanger, Amanda N.; Borchert, Thomas; Bryant, Emma; Burger, Alane S.; Dixon, Laura J.; Dutcher, Christina D.; et al. (Journal of Anxiety Disorders, 2025)
Background: This paper reports on the outcomes of a proof-of-principle study for the Exposure Therapy Consortium, a global network of researchers and clinicians who work to improve the effectiveness and uptake of exposure therapy. The study aimed to test the feasibility of the consortium's big-team science approach and test the hypothesis that adding post-exposure processing focused on enhancing threat reappraisal would enhance the efficacy of a one-session large-group interoceptive exposure therapy protocol for reducing anxiety sensitivity. Methods: The study involved a multi-site cluster-randomized controlled trial comparing exposure with post-processing (ENHANCED), exposure without post-processing (STANDARD), and a stress management intervention (CONTROL) in students with elevated anxiety sensitivity. Feasibility was assessed using site performance metrics (e.g., timeline, sample size, missing data). Efficacy was assessed up to 1-month follow-up using the Anxiety Sensitivity Index-3. Results: Despite challenges posed by unforeseen global crises, a standardized protocol for screening, assessment, and treatment at 12 research sites across four continents was successfully implemented, resulting in a total sample size of 400 with minimal missing data. Challenges in recruitment and adherence to the projected timelines were encountered. Significant reductions in anxiety sensitivity were observed in all conditions. Contrary to hypotheses, group differences were only observed at post-treatment, when ENHANCED and CONTROL outperformed STANDARD but were not significantly different from each other. Conclusions: This study demonstrates the feasibility of the Exposure Therapy Consortium. Findings raise questions regarding the efficacy of large group exposure interventions and underscore the importance of careful research site selection and an iterative approach to treatment development.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Anxiety sensitivity; Augmentation; Big-team science; Experiment; Exposure therapy; Interoceptive exposure